Implementation of Six Sigma Method in Small and Medium Enterprises (SMEs) (Case Study on CV. Berkah Abadi) - M. ABDILLAH RORKE ILYASA; MERITA BERNIK; BUDI HARSANTO (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2016)
The increasing economic growth in Indonesia encourages the growth of SMEs (Small and Medium Enterprises). This condition results in the intense competition among similar SMEs. This encourages companies to always produce quality products in order to meet customers’ satisfaction. One of the methods to control the quality is by using Six Sigma. Six sigma is a method of improving the quality towards the target of 3.4 failures per million opportunities for each production of goods and services. Six sigma is divided into two methods, namely DMAIC (Define, Measure, Analyze, Improve, Control) and DMADV (Define, Measure, Analyze, Design, Verify). Six Sigma can be implemented not only for big companies but also for SMEs. This study was conducted to determine the application of quality control aspect of Six Sigma in CV. Berkah Abadi as an SME in producing shoes under the name BNA. This study utilized DMAIC method. By using Six Sigma, it can be seen that the sigma value in the production process of CV Berkah Abadi is 3,274 with the possibility of error products contained is 38758.87 in a million occasions. In the application of Six Sigma in this study, there are six causes of defective products, namely untidy glue application (41.7%), stains (23.8%), squiggled pattern (11.9%), untidy stitches neat (10.4%), wrinkles (8.9%) and torn materials (2.9%).